Households' response to the wealth effects of inflation - Philip Schnorpfeil; Michael Weber; Andreas Hackethal (Goethe University Frankfurt, Center for Financial Studies (CFS), 2024)
We study households' response to the redistributive effects of inflation combining bank data with an information experiment during historic inflation. Households are generally well-informed about inflation and concerned about its wealth impact; yet, while knowledge about inflation eroding nominal assets is widespread, most households are unaware of nominal-debt erosion. When informed about the latter, households view nominal debt more positively and increase estimates of their real net wealth. These changes causally affect actual consumption and hypothetical debt decisions. Our findings suggest real wealth mediates the sensitivity of consumption to inflation once households are aware of the wealth effects of inflation.
Keywords: D12; D14; D83; D84; E21; E31; E52; 330; Inflation Beliefs; Information Treatment; Consumption; Monetary Policy